The mediating role of parent-child conflict in the relationship between self-differentiation and social anxiety - Mahbobeh , Bakhshaei; Azadi , Mehran (Applied Family Therapy Journal (AFTJ), 2020)
Aim: This study aimed to investigate the mediating role of parent-child conflict in the relationship between self-differentiation and social anxiety. Method: This is a descriptive correlational study. This study's statistical population was female high school students who study in the 2nd district of Tehran in the academic year of 2018-19. Sampling was performed by random multi-stage clustering. First, three high schools were selected from the girls' high schools in District 2 of Tehran. Then, two classes were selected from each high school according to their educational levels. A sample of 287 students was selected by random cluster sampling, and they answered the Differentiation Questionnaire (Scorn, 1998), Parent-Child Conflict Tactics (‎Straus, 1990), and Social Anxiety Questionnaire (Liebowitz, 1999). Results: The results of the correlation coefficient showed that there was a significant correlation between the total score of differentiation (r = -0.201) as well as subscales of my position (r = -0.256), emotional escape (r = -0.203), and fusion with others (r = -0.180) with social anxiety at the level of 0.01. Also, there was a significant correlation between the subscale of emotional responsiveness (r =-0.156) and social anxiety at the level of 0.05. There was also a correlation between parent-child conflict and social anxiety (r = 0.188) and between verbal aggression subscale (r = 0.186) and physical aggression subscale (r = 0.179) with social anxiety. Besides, the path coefficient model results showed a significant direct relationship between differentiation and social anxiety and between parent-child conflict and social anxiety (p = 0.01). Still, there was no significant direct effect between differentiation and parent-child conflict (p